Phenolic Derivatives from Fruits of Dipteryx lacunifera DUCKE and Evaluation of Their Antiradical Activities - Vieira Junior, Gerardo Magela [UNESP]; Sotssa, Cleyton Marcos de A.; Cavalheiro, Alberto José [UNESP]; Lago, Joao Henrique G.; Chaves, Mariana H. (Wiley-v C H Verlag Gmbh, 2008)
The fruits of Dipteryx lacunifera, known as 'fava de morcego' and 'garampara', comprise pleasant tasting kernels that contain high amounts of fatty acids (mainly oleic acid) and are commonly consumed by inhabitants of the northeast of Brazil. In the present study, the crude EtOH extract of the fruit kernels was separated into hexane-, Et(2)O-, AcOEt-, and H(2)O-soluble fractions. The Et(2)O fraction was found to exhibit the highest 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activity in vitio, and was subjected to further fractionation. Column chromatography over silica gel and Sephadex LH-20, followed by preparative HPLC-C(18), afforded (-)-eriodictyol (1), (-)-butin (2), luteolin (3), 3',4',7- trihydroxyflavone(4), butein (5). and sulfuretin (6). The antiradical activities of compounds 1, 2, 4, and 6. together with the positive controls rutin,. butylated hydroxy toluene (BHT), and tert-butylhydroquinone (TBHQ), were evaluated with the DPPH assay and were found to decrease in the order rutin > 4 > 1 > 6 > 2 > TBHQ > BHT.